Eksplorasi Kebutuhan Pengembangan Buku Saku Deiksis Sosial Bahasa Mandarin bagi Pemelajar Pemula - Novia Chyntia Dewi; Tri Budianingsih; Sri Harini Ekowati (Universitas Mulawarman, 2023)
This article explores the needs of Chinese beginner learners regarding a pocket guide to using Chinese social deixis. The method used is descriptive qualitative with data collection techniques in the form of questionnaires. The questionnaire was distributed through Google Forms to 40 first and second-semester students or the equivalent of CEFR A1 and A2 standards or HSK levels 1 and 2 in the Chinese Language Education Study Program at the State University of Jakarta. The results of this study are 73.1% of students have a non-Chinese background, and 92.9% of students' parents do not speak Chinese, so students can only learn Chinese in the campus environment. 53.8% of students have difficulty translating and interpreting social deixis that appears in texts and dialogues. In Chinese communication, 65.4% of students feel insecure about the accuracy of the greetings they use. 96.6% of students stated that they needed a guidebook for using social deixis by compiling a list of greeting words based on the textbook's chapter order.